Pengaruh Online Store Beliefs Terhadap Impulse Buying Konsumen Secara Online Pada Duiphijab Store Di Tenggarong - Kaulah, Nida; Jais, Achmad; S, Syahruddin (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2017)
This research was to analyze The Influence of Online Store Beliefs to Impulse Buying (Consumer Purchase) Online at the Duiphijab Store In Tenggarong. The analysis tool used in this research is simple regression method with the help of SPSS 20.1 For Window, with population number 30 responden and sample number 30 responders. R value is 56% it means there is relationship between Online store beliefs variable to impulse buying. And R square value is 0,314 it means 31,4% consumer impluse buying affected by online store beliefs and 68,6% consumer impluse buying affected by another variable such us location, price, consumer perseption. From the research results it can be concluded that there is a significant influence between Online Store Beliefs to Impulse Buying consumers online at Duiphijab Store In Tenggarong. Thus the hypothesis proposed by researchers in this study are: "That Online Store Beliefs significantly influence Impulse Buying consumers online at Duiphijab Store In Tenggarong" accepted and proven true. Keywords: Beliefs, Impulse Buying